Gm and Km allotypes and Typhoid Fever (1996)
ABSTRACT: Gm and Km allotypes of immunoglobulins were determined in children with typhoid fever (Cases), in children without infectious diseases (Con-1), and in children with fever but no Salmonella in their blood or bone marrow (Con-2). Children were sampled from the urban population of Santiago; and they belonged to the low and low-middle socioeconomic strata. Cases had a higher frequency of [f;(-);b1,b3 or 3;(-);5,13] G1m, G2m, G3m haplotype than Con-1 and Con-2. Con-1 and Con-2 did not differ in their Gm haplotype or Km allele frequencies, but they differed in phenotype distribution. Con-1 deviated from Hardy-Weinberg equilibrium for Km due to a lack of Km 1-1 homozygotes. The relationship among these results, the ethnic origin of Chileans, and the differential susceptibility to typhoid fever are discussed.